2012
DOI: 10.5923/j.ajmms.20120204.02
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Pill 3-drug Combination of Lamivudine, Nevirapine and Zidovudine on Blood Parameters and Liver Histology in Female Wistar Rats

Abstract: Due to the stigma associated with HIV infection, HIV infected persons in Nigeria, have been found to remove the packs of their drugs and transferring the contents into non antiretroviral drug containers especially multivitamin containers, as a result unwary individuals have stumbled on such drugs and accidentally consumed it eventually leading to a host of complains such as dizziness, vague dreams, cramps etc. We therefore decided to study the effects of a single pill 3-drug combination of Lamivudine, Nevirapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The findings in this study agree with the findings of Agarwal et al, 2010 were a high incidence of zidovudine induced anaemia was reported amongst Indian patients. This effect of ZDV on Red blood cells and platelets observed in this study can be attributed to its myelosuppressive ability that has been well established [2,1,42].…”
Section: Discussionsupporting
confidence: 65%
“…The findings in this study agree with the findings of Agarwal et al, 2010 were a high incidence of zidovudine induced anaemia was reported amongst Indian patients. This effect of ZDV on Red blood cells and platelets observed in this study can be attributed to its myelosuppressive ability that has been well established [2,1,42].…”
Section: Discussionsupporting
confidence: 65%